The performance of the financial sector during the COVID-19 pandemic - Savitri, Enni; Abdullah, Nik Herda Nik; Musfi, Putri Nabila (Business: Theory and Practice, 2022)
The financial report of a company reveals how successfully it is competing and operating its business. The financial report serves as a guide for management in terms of making decisions that will help the company enhance its performance. The purpose of this study is to examine the effects of intellectual capital and enterprise risk management on the financial performance of businesses, with corporate governance serving as a moderating factor. The annual reports of 91 financial sector companies listed on the Indonesia Stock Exchange were analysed in this study. The data is based on a fouryear period, from 2016 to 2020. Panel data regression and moderated regression analysis were used in this study, which was conducted using Eviews statistical software. The findings indicate that intellectual capital has a negative effect on financial performance. Meanwhile, enterprise risk management was found to have no effect on financial performance. In addition, the findings show that corporate governance represented by independent commissioners can moderate the negative effect of intellectual capital on financial performance and institutional ownership has a moderating effect on intellectual capital and enterprise risk management on financial performance. The research indicates that corporations should increase their intellectual capital and risk management disclosure, as well as aiming for great corporate governance.